Structure and stability of boron doped titanate nanotubes and nanowires. (April 2017) - Buchholcz, Balázs; Varga, Erika; Varga, Tamás; Plank, Kamilla; Kiss, János; Kónya, Zoltán
Abstract: Boron doped titanate nanoparticles were prepared from protonated (H-form) titanate nanotubes (TiONT) and nanowires (TiONW). The chemical nature and morphology of boron were monitored by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and transmission electron microscopy (TEM). XPS proved that significant part of the boron incorporated into interstitial position (TiOB) of titanate nanotubes and nanowires, while a smaller part of the boron formed boron titanates via ion-exchange process. In the case of titanate nanotubes the presence of boron induced morphological (tubular to rod-like) and structural (trititanate to anatase) changes. These effects were not so pronounced on titanate nanowires. Highlights: Boron incorporates in interstitial position in titanates. Boron undergoes an ion-exchange process during formation of boron titanates. Boron may induce the transformation of trititanate structure to anatase. In the case of nanowires, boron does not promote anatase phase formation.